An experimental study of gasification kinetics during steam activation of a spent tyre pyrolysis char. Issue 4 (August 2021) - Preciado-Hernandez, Jorge; Zhang, Juan; Jones, Isabelle; Zhu, Mingming; Zhang, Zhezi; Zhang, Dongke
Abstract: The pyrolysis char, produced in an industrial scale retort process, was subjected to steam activation under atmospheric pressure to assess carbon conversion as a factor of variations in temperature (750–1050 °C), concentration of activation agent (33.3–66.7 vol% steam/N2 mixture), and reaction time (0.5–4 h). The BET surface area was determined using N2 adsorption and compare against carbon conversion. The steam gasification reaction was shown to be kinetically controlled under the conditions studied. The behaviour of the solid-gas gasification reaction rate was modelled using non-catalytic heterogeneous models: Dutta model, random pore model, shrinking core model, and volumetric model. The experimental data were fit best by the volumetric model, indicating that carbon-steam gasification reactions throughout the particle were uniform and the gasification reaction was not influenced by the structure of the pores. The pre-exponential factor, activation energy and reaction order of the volumetric model were 5.42 × 10 −3 s −1, 114 kJ mol −1 and 0.6, respectively, determined by non-linear least-squares fitting of the model to the experimental data. Graphical Abstract: ga1 Highlights: The steam gasification kinetics of spent tyre pyrolysis char was studied. The steam gasification was kinetically controlled under the studied conditions. Higher temperature, time and steam concentration led to greater carbon conversion. The volumetric model was found to best describing the gasification rate behaviour. The calculated kinetic parameters are n 0.6, E 114.3 kJ mol −1 and A 5.42 × 10 −3 s −1 .